INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON PERFORMANCE OF EMPLOYEES PT. CITRA SURVEYOR INDONESIA - Ahmaluddin .; Ahmad Hudalil (University of Sang Bumi Ruwa Jurai, 2022)
This study used 26 respondents from PT. Indonesian Surveyor Image. There are three variables in this study, namely: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where Leadership (X1) and Work Environment (X2) are independent variables and Employee Performance (Y) is the dependent variable. From the results of data processing, it has been found that the answers to the hypothesis are as follows; there is an influence of leadership (X1) on employee performance (Y), with a level of influence (R-square) of 79.1%, which means that leadership has an influence of 79.1% on employee performance. There is an influence between the Work Environment (X2) on Employee Performance (Y), with an influence level of 99.1% which means that the Work Environment has an influence of 99.1% on Employee Performance. There is an influence between Leadership (X1), Work Environment (X2) and Employee Performance (Y), with an influence level of 99.1% which means that Leadership and Work Environment have an influence of 99.1% on Employee Performance.